VICE PRESIDENT'S POWER AND ROLE IN INDONESIAN GOVERNMENT POST AMENDMENT 1945 CONSTITUTION - Roziqin Roziqin (AL WASATH Jurnal Ilmu Hukum, 2020)
Politicians are fighting over the position of Vice President. However, after becoming Vice President, they could not be active. The Vice President's role is only as a spare tire. Usually, he would only perform ceremonial acts. The exception was different when the Vice President was Mohammad Hata and Muhammad Jusuf Kalla. Therefore, this paper will question: What is the position of the President in the constitutional system? What is the position of the Vice President of Indonesia after the amendment of the 1945 Constitution? Furthermore, how is the role sharing between the President and Vice President of Indonesia? This research uses the library research method, using secondary data. This study uses qualitative data analysis methods in a prescriptive-analytical form. From the research, the writer found that the President is assisted by the Vice President and ministers in carrying out his duties. The President and the Vice President work in a team of a presidential institution. From time to time, the Indonesian Vice President's position has always been the same to assist the President. The Vice President will replace the President if the President is permanently unavailable or temporarily absent. With the Vice President's position who is directly elected by the people in a pair with the President, he/she is a partner, not subordinate to the President. Moreover, due to his/her capacity and support from his/her team, the Vice President must be empowered to benefit the nation and state.